Sarcocystis sinensis is the most prevalent thick-walled Sarcocystis species in beef on sale for consumers in Germany - Moré, Gastón Andrés (2014)
Bovines are intermediate hosts of Sarcocystis cruzi, Sarcocystis hirsuta, and Sarcocystis hominis, which use canids, felids, or primates as definitive hosts, respectively. Cattle represent also intermediate hosts of Sarcocystis sinensis, but the definitive hosts of this parasite are not yet known. Sarcocystosis in cattle is frequently asymptomatic. The infection is characterized by the presence of thin-walled (S. cruzi) or thick-walled muscle cysts or sarcocysts (S. hominis, S. sinensis, and S. hirsuta). Recent reports suggest high prevalence of the zoonotic S. hominis in beef in Europe. We therefore aimed at differentiating Sarcocystis spp. in beef offered to consumers in Germany using molecular and microscopical methods, focusing on those species producing thick-walled sarcocysts. A total of 257 beef samples were obtained from different butcheries and supermarkets in Germany and processed by conventional and multiplex real-time PCR. In addition, 130 of these samples were processed by light microscopy and in 24.6 % thick-walled cysts were detected. Transmission electron microscopical analysis of six of these samples revealed an ultrastructural cyst wall pattern compatible with S. sinensis in five samples and with S. hominis in one sample. PCR-amplified 18S ribosomal DNA (rDNA) fragments of 28 individual thick-walled cysts were sequenced, and sequence identities of ≥98 % with S. sinensis (n = 22), S. hominis (n = 5) and S. hirsuta (n = 1) were observed. Moreover, nine Sarcocystis sp. 18S rDNA full length gene sequences were obtained, five of S. sinensis, three of S. hominis, and one of S. hirsuta. Out of all samples (n = 257), 174 (67.7 %) tested positive by conventional PCR and 179 (69.6 %) by multiplex real-time PCR for Sarcocystis spp. Regarding individual species, 134 (52 %), 95 (37 %), 17 (6.6 %), and 16 (6.2 %) were positive for S. cruzi, S. sinensis, S. hirsuta, and S. hominis, respectively. In conclusion, S. sinensis is the most prevalent thick-walled Sarcocystis species in beef offered for consumption in Germany. Further studies are needed to identify the final host of S. sinensis as well as the potential role of this protozoan as a differential diagnosis to the zoonotic species S. hominis.